Media E-Book Cerita Bergambar Meningkatkan Autonomous Learning dan Minat Baca Siswa Sekolah Dasar - Ni Made Omy Yundari; Maria Goreti Rini Kristiantari; Dewi Anzelina (Universitas Pendidikan Ganesha, 2025)
Low reading interest and autonomous learning among elementary students are challenges in learning the Indonesian language. This study aimed to develop, validate, and measure the effectiveness of a picture story E-Book to enhance autonomous learning and reading interest among third-grade students at elementary school. The research applied the Research and Development (R&D) method using the ADDIE model, involving three experts (content, instructional design, and media) and 24 students as 24 students as effectiveness subjects, 3 students for individual trials, and 9 students for small group trials. Data analysis was conducted using descriptive quantitative and inferential methods. Data analysis was conducted using descriptive quantitative and inferential methods. Data were collected using multiple-choice tests, questionnaires, interviews, and observations. Validation results showed very good categories, with scores of 94.79% for content, 100% for instructional design, and 92.50% for media. The effectiveness test used a paired sample t-test, showing tcount = 12.243 > ttable = 2.069 at a 5% significance level, indicating a significant difference before and after using the E-Book. The study concluded that the picture story E-Book effectively enhanced students' reading interest and autonomous learning. The study's implications support the development of innovative technology-based learning to improving Indonesian language learning.